Calculation of the probability integral indicator of the level of air pollution - Alekseevna, Tunakova Yulia; Vladimirovna, Novikova Svetlana; Rifgatovich, Shagidullin Artur (International Conference “Environmental Engineering”, 2017)
This article describes the method for calculation of probability integral indicator of the level of air pollution. The calculation is based on information on easily identifiable meteorological parameters by using neural network technology. This is especially true in terms of space-time constraints for existing network stations for environmental monitoring system observations.